Selective auxin agonists induce specific AUX/IAA protein degradation to modulate plant development - Vain, Thomas; Raggi, Sara; Ferro, Noel; Barange, Deepak Kumar; Kieffer, Martin; Ma, Qian; Doyle, Siamsa M; Thelander, Mattias; Pařízková, Barbora; Novák, Ondřej; Ismail, Alexandre; Enquist, Per-Anders; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Auxin phytohormones control most aspects of plant development through a complex and interconnected signaling network. In the presence of auxin, AUXIN/INDOLE-3-ACETIC ACID (AUX/IAA) transcriptional repressors are targeted for degradation by the SKP1-CULLIN1-F-BOX (SCF) ubiquitin-protein ligases containing TRANSPORT INHIBITOR RESISTANT 1/AUXIN SIGNALING F-BOX (TIR1/AFB). CULLIN1-neddylation is required for SCFTIR1/AFB functionality, as exemplified by mutants deficient in the NEDD8-activating enzyme subunit AUXIN-RESISTANT 1 (AXR1). Here, we report a chemical biology screen that identifies small molecules requiring AXR1 to modulate plant development. We selected four molecules of interest, RubNeddin 1 to 4 (RN1 to -4), among which RN3 and RN4 trigger selective auxin responses at transcriptional, biochemical, and morphological levels. This selective activity is explained by their ability to consistently promote the interaction between TIR1 and a specific subset of AUX/IAA proteins, stimulating the degradation of particular AUX/IAA combinations. Finally, we performed a genetic screen using RN4, the RN with the greatest potential for dissecting auxin perception, which revealed that the chromatin remodeling ATPase BRAHMA is implicated in auxin-mediated apical hook development. These results demonstrate the power of selective auxin agonists to dissect auxin perception for plant developmental functions, as well as offering opportunities to discover new molecular players involved in auxin responses.
Keywords: proteolýza; geneticky modifikované rostliny; Arabidopsis Proteins; transkripční faktory; Plants, Genetically Modified; Transcription, Genetic; Indoleacetic Acids; F-Box Proteins; F-box proteiny; Transcription Factors; signální transdukce; proteinligasy komplexu SCF; Signal Transduction; proteiny huseníčku; protein NEDD8; genetická transkripce; Plant Development; kyseliny indoloctové; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; receptory buněčného povrchu; SKP Cullin F-Box Protein Ligases; Receptors, Cell Surface; Arabidopsis; regulátory růstu rostlin; vývoj rostlin; semenáček; NEDD8 Protein; Seedlings; Plant Growth Regulators; Proteolysis